Parallel computational fluid dynamics trends and applications : proceedings of the Parallel CFD 2000 Conference - Parallel CFD 2000 Conference (2000 : Trondheim, Norway); Jenssen, C. B. (Carl B.) (New York : Elsevier, 2001)
Parallel CFD 2000, the Twelfth in an International series of meetings featuring computational fluid dynamics research on parallel computers, was held May 22-25, 2000 in Trondheim, Norway. Following the trend of the past conferences, areas such as numerical schemes and algorithms, tools and environments, load balancing, as well as interdisciplinary topics and various kinds of industrial applications were all well represented in the work presented. In addition, for the first time in the Parallel CFD conference series, the organizing committee chose to draw special attention to certain subject areas by organizing a number of special sessions. We feel the emphasis of the papers presented at the conference reflect the direction of the research within parallel CFD at the beginning of the new millennium. It seems to be a clear tendency towards increased industrial exploitation of parallel CFD. Several presentations also demonstrated how new insight is being achieved from complex simulations, and how powerful parallel computers now make it possible to use CFD within a broader interdisciplinary setting. Obviously, successful application of parallel CFD still rests on the underlying fundamental principles. Therefore, numerical algorithms, development tools, and parallelization techniques are still as important as when parallel CFD was in is infancy. Furthermore, the novel concepts of affordable parallel computing as well as metacomputing show that exciting developments are still taking place. As is often pointed out however, the real power of parallel CFD comes from the combination of all the disciplines involved: Physics, mathematics, and computer science. This is probably one of the principal reasons for the continued popularity of the Parallel CFD Conferences series, as well as the inspiration behind much of the excellent work carried out on the subject. We hope that the papers in this book, both on an individual basis and as a whole, will contribute to that inspiration. Further details of Parallel CFD'99, as well as other conferences in this series, are available at <SURL>http://www.parcfd.org</SURL>.
Cover -- Table of Contents -- Part 1: Invited Papers -- Chapter 1. Perspectives and Limits of Parallel Computing for CFD Simulation in the Automotive Industry -- Chapter 2. Application of Navier-Stokes Methods to Predict Votex-Induced Vibrations of Offshore Structures -- Chapter 3. Dynamics Controlled by Magnetic Fields: Parallel Astrophysical Computations -- Chapter 4. A Software Framework for Easy Parallelization of PDE Solvers -- Chapter 5. Parallel Computing of Non-equilibrium Hypersonic Rarefied Gas Flows -- Chapter 6. Large-Eddy Simulations of Turbulence: Towards Complex Flow Geometries -- Chapter 7. Direct Numerical Simulations of Multiphase Flows -- Chapter 8. Aerodynamic Shape Optimization and Parallel Computing Applied to Industrial Problems -- Part 2: Affordable Parallel Computing -- Chapter 9. Accurate Implicit Solution of 3-D Navier-Stokes Equations on Cluster of Work Stations -- Chapter 10. Performance of a Parallel CFD-Code on a Linux Cluster -- Chapter 11. Utilising Existing Computational Resources to Create a Commodity PC Network Suitable for Fast CFD Computation -- Chapter 12. Use of Commodity Based Cluster for Solving Aeropropulsion Applications -- Chapter 13. Using a Cluster of PC's to Solve Convection Diffusion Problems -- Chapter 14. Building PC Clusters: An Object-oriented Approach -- Chapter 15. The Solution of Pitching and Rolling Delta Wings on a Beowulf Cluster -- Part 3: Performance Issues -- Chapter 16. Serial and Parallel Performance Using a Spectral Code -- Chapter 17. On the Design of Robust and Efficient Algorithms that Combine Schwartz Method and Multilevel Grids -- Chapter 18. 2-D To 3-D Conversion for Navier-Stokes Codes: Parallelization Issues -- Part 4: Load Balancing -- Chapter 19. Dynamic Load Balancing in International Distributed Heterogeneous Workstation Clusters -- Chapter 20. Dynamic Load Balancing for Unstructured Fluent -- Chapter 21. Parallel Computing and Dynamic Load Balancing of ADPAC on a Heterogeneous Cluster of Unix and NT Operating Systems -- Chapter 22. Efficient Techniques for Decomposing Composite Overlapping Grids -- Part 5: Tools and Environments -- Chapter 23. Computer Load Measurement for Parallel Computing -- Chapter 24. Numerical Algorithms and Software Tools for Efficient Meta-computing -- Chapter 25. Mixed C++/Fortran 90 Implementation of Parallel Flow Solvers -- Chapter 26. COUPL+ : Progress Towards an Integrated Parallel PDE Solving Environment -- Chapter 27. Implementations of a Parallel 3D Thermal Convection Software Package -- Chapter 28. Development of a Common CFD Platform-UPACS- -- Part 6: Numerical Schemes and Algorithms -- Chapter 29. Numerical Investigation of Viscous Compressible Gas Flows by Means of Flow Field Exposure to Acoustic Radiation -- Chapter 30. A New Low Communication Parallel Algorithm for Elliptic Partial Differential Equations -- Chapter 31. Parallel Multigrid on Cartesian Meshes with Complex Geometry -- Chapter 32. Parallelisation of a CFD Code: The Use of Aztec Library in the Parallel Numerical Simulation of Extrusion of Aluminium -- Chapter 33. An Efficient Highly Parallel Multigrid Method for the Advection Operator --T$
Includes bibliographical references.
Keywords: Fluid dynamics -- Data processing -- Congresses; Parallel processing (Electronic computers) -- Congresses; Electronic books